Efektivitas Katalis CaO/SiO2 dari Limbah Sekam Padi dan Cangkang Telur dengan Variabel Waktu Reaksi untuk Sintesis Biodiesel - Sitanggang, Christin Octaviani; Perdani, Meka Saima; Umam, Hilman Imadul; Fadilla, Amalia Dian; Nurhana, Eti Ayu (Jurnal Teknik Kimia USU, 2026)
This research focusses on the synthesis of biodiesel as an altenative fuel to replace diesel oil which can be produced from vegetable oil or animal fat as renewable dan sustainable fuel. This study was conducted to determine the effect of stirring time in the manufacture of biodiesel on the effectiveness of the CaO/SiO2 catalyst from egg shell waste dan rice husks in the transesterification process. The control variables in this study were raw materials taken from rice husk waste dan chicken egg shell waste, and the mole ratio of used cooking oil: methanol used was 9:1. The variation of stirring time used was 30 minutes, 60 minutes, 90 minutes, 120 minutes, 150 minutes with a stirring speed of 450 rpm at 65ºC. The results showed that the optimal time in this study was 150 minutes with a biodiesel yield of 63.64%.